2018
DOI: 10.1080/24750573.2018.1426696
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine-attenuated cognitive and social deficits in subchronic MK-801 model of schizophrenia in rats

Abstract: INTRODUCTION: Schizophrenia is one of the most severe psychiatric disorders with about 1% prevalence. It has been proved that glutamatergic N-methyl-D-aspartate (NMDA) receptor antagonists such as MK-801 and phencyclidine cause schizophrenia-like behaviours in rodents. Agmatine is an endogenous amine synthesized from decarboxylation of arginine and has been thought to be a neurotransmitter/neuromodulator. It binds to imidazoline and alfa adrenergic receptors and blocks cation channelled receptors, such as nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In literature it has been seen that MK-801 impaired PPI at the doses 0.1-1 mg/kg in rats. The disruptive effect of MK-801 on PPI has been confirmed by our previous studies in 0.2 mg/kg dose of MK-801 [17,18]. In accordance with previous studies, our results showed that MK-801 administration disrupted sensorimotor gating in rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In literature it has been seen that MK-801 impaired PPI at the doses 0.1-1 mg/kg in rats. The disruptive effect of MK-801 on PPI has been confirmed by our previous studies in 0.2 mg/kg dose of MK-801 [17,18]. In accordance with previous studies, our results showed that MK-801 administration disrupted sensorimotor gating in rats.…”
Section: Discussionsupporting
confidence: 92%
“…It has been indicated that subchronic administration of PCP generally impairs recognition memory in rodents after a week washout period whereas subchronic MK-801 administration has conflicting results for NORT [20]. It has been reported in previous studies that 14 days (0.05, 0.1 and 0.2 mg/kg) and 28 days (0.25 mg/kg) daily MK-801 administrations did not impair recognition memory at NORT in rats [12,18,20]. Our results showed that 14 days daily administration did not affect NORT performance while 7 days bi-daily injections deteriorated recognition memory in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly to acute treatment, chronic and subchronic MK-801 treatment leads to cognitive deficits (Latysheva and Rayevsky, 2003; Stefani and Moghaddam, 2005; Rujescu et al, 2006; Li et al, 2011; Xiu et al, 2014; Liu et al, 2017; Unal et al, 2018). In addition, chronic MK-801 treatment leads to sensorimotor gating and social interaction deficits, although there are controversial results on locomotor activity (Latysheva and Rayevsky, 2003; Eyjolfsson et al, 2006; Xiu et al, 2014; Unal et al, 2018). Another study showed that chronic MK-801 induce increased anxiety-like behavior and working memory deficits, which was accompanied by degenerative changes of myelin sheaths, decreased white matter and corpus callosum volume (Xiu et al, 2014).…”
Section: Pharmacological Approaches To Induce Nmdar Hypofunctionmentioning
confidence: 99%
“…This substance was used to induce the experimental schizophrenia in laboratory animals [35,36]. Agmatine attenuates cognitive and behavioral deficiency in rats with experimental phencyclidine-induced schizophrenic manifestations [37].…”
Section: The Involvement Of the Imidazoline System In The Mediation Omentioning
confidence: 99%